2015
DOI: 10.1002/piq.21197
|View full text |Cite
|
Sign up to set email alerts
|

Managerial Practices and Organizational Conditions That Encourage Employee Growth and Development

Abstract: This paper focuses on seven major managerial practices and three negative conditions that must be managed to enhance employee growth and development. These managerial practices and conditions have significant potential for human resource development practitioners and performance improvement technologists by providing new perspectives to improve employee performance through employee growth and development activities. Surveys measuring employee perceptions of manager behaviors were administered to 503 MBA and Ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Several empirical studies show a positive relationship between specific human-resource practices, and employee effort (Gilley, Gilley, Jackson & Lawrence, 2015). Walsh and Tseng (1998) have showed that employees' participation has a positive effect on their effort.…”
Section: Mediating Role Of Effort In the Relationship Between Hpws Anmentioning
confidence: 99%
“…Several empirical studies show a positive relationship between specific human-resource practices, and employee effort (Gilley, Gilley, Jackson & Lawrence, 2015). Walsh and Tseng (1998) have showed that employees' participation has a positive effect on their effort.…”
Section: Mediating Role Of Effort In the Relationship Between Hpws Anmentioning
confidence: 99%
“…It is very important that the leadership in the military organization be able to communicate and convince subordinates to ensure the success of any reform initiative to enhance procurement decision and improve overall performance. The leaders must maximize the potential of others and motivate them to achieve common goals and be able to manage individual and group performance with an understanding of group dynamics and team building (Gilley et al, 2015). Leaders that are capable of communicating with staff always succeed in implementing reform within the organization (Gilley et al, 2015).…”
Section: Leadership Communicationmentioning
confidence: 99%
“…The leaders must maximize the potential of others and motivate them to achieve common goals and be able to manage individual and group performance with an understanding of group dynamics and team building (Gilley et al, 2015). Leaders that are capable of communicating with staff always succeed in implementing reform within the organization (Gilley et al, 2015). Zohar and Polachek (2014), Dobre (2013) and Morphitou (2017) found that there is a significant relationship between leadership communication in organization and organizational performance.…”
Section: Leadership Communicationmentioning
confidence: 99%
“…While the careers literature focuses on individuals' impetus for learning, managers play a crucial role in promoting growth in followers, particularly for those who may not have access to other, perhaps more formalized, opportunities for development (Gilley et al, 2015). Some functional line manager behaviors can promote growth through well-studied practices including coaching and feedback for task performance (Sue-Chan et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Review of the literature While many studies are concerned directly with employer centric outcomes such as engagement and organizational citizenship behavior, studies of managerial behaviors that facilitate employee growth and development are less common (Gilley et al, 2015;Kara et al, 2013). So too are studies on how growth and development can then support further flourishing in employees, such as well-being and engagement (Barrio, 2013).…”
Section: Introductionmentioning
confidence: 99%